Determination of the Physical Properties of Oil Sands Components using Scanning Probe Microscopy. Issue 1754 (16th March 2015) - Gaikwad, Ravi; Abraham, Tinu; Hande, Aharnish; Bakhtiari, Fatemeh; Das, Siddhartha; Thundat, Thomas
ABSTRACT: Atomic force microscopy is employed to study the structural changes in the morphology and physical characteristics of asphaltene aggregates as a function of temperature. The exotic fractal structure obtained by evaporation-driven asphaltene aggregates shows an interesting dynamics for a large range of temperatures from 25 ° C to 80 ° C. The changes in the topography, surface potential and adhesion are unnoticeable until 70 ° C. However, a significant change in the dynamics and material properties is displayed in the range of 70 ° C - 80 ° C, during which the aspahltene aggregates acquire 'liquid-like' mobility and fuse together. This behaviour is attributed to the transition from the pure amorphous phase to a crystalline liquid phase which occurs at approximately 70 ° C as shown by using Differential Scanning Calorimetry (DSC). Additionally, the charged nature of asphaltenes and bitumen is also explored using kelvin probe microscopy. Such observations can lead to the development of a rational approach to the fundamental understanding of asphaltene aggregation dynamics and may help in devising novel techniques for the handling and separation of asphaltene aggregates using dielectrophoretic methods.